Social Capital as the Foundation for Strengthening Community Economy through the Sustainability of Traditional Dance in Cultural Tourism - Lia Dama Yanti; Pujiarti Pujiarti; Andy Andy (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study examines the role of social capital in strengthening local community economy and its impact on the sustainability of traditional dance in the context of cultural tourism. The research problem is rooted in the declining interest in traditional arts and the need for community-based strategies to ensure their continuity. The objective of this study is to analyse how social networks, social trust, and collective norms influence the local community economy, which in turn supports the sustainability of traditional dance. Using a quantitative approach with SEM-PLS analysis, data were collected from 150 respondents selected based on the rule of thumb method. The findings reveal that local community economy has a significant positive effect on the sustainability of traditional dance, while social networks and social trust significantly strengthen the community economy. However, direct effects of social capital on dance sustainability were not significant, indicating the mediating role of local economy. This study contributes to the literature by offering a new perspective that integrates social capital and cultural preservation within community-based economic empowerment. Practically, the results highlight the need for policies and programs that strengthen community economy as a strategy for preserving cultural heritage. Keywords: Social capital; community economy; cultural tourism; traditional dance sustainability; SEM-PLS